GPS, borehole strain and tilt data - 24 December 2018 eruptive intrusion Etna volcano - Aloisi, Marco; Bonaccorso, Alessandro; Cannavò, Flavio; Currenti, Gilda; Gambino, Salvatore (figshare, 2019)
On the early morning of 24 December 2018, after two months of Strombolian activity, Mt Etna was suddenly penetrated by a violent dyke intrusion that opened an eruptive fissure and continued to propagate southward for more than ten hours. This dataset includes: - raw GPS data from 24 to 25 December 2018 (Zip archive) - borehole strain data for the 24 December (positive variation = compression; negative variation = dilatation; [counts]) - borehole tilt data (biaxial) for the 24 December (negative variation = uplift; [microstrain]).
Keywords: Geophysics; FOS: Earth and related environmental sciences; FOS: Earth and related environmental sciences